(untitled) (Third Sector Social Economic Review, 2023)
During the COVID-19 outbreak, supply chain, and especially logistics companies are vulnerable to the risks confronted and strive to sustain and improve their resilience by utilizing technology. Accordingly, the objective of this study is to conduct an analysis of the ways in which research on technology and resilience has been conducted in the context of supply chains, and more specifically in the context of logistics organizations. An extensive review of the relevant literature is going to be examined. In this sense, the purpose of this study is to address the current technology and resilience knowledge gap in the logistics industry by employing a literature review. Our contribution is to divide the studies in the literature into three such as existing literature reviews, original research (primary focus and/or key variables are/are not technology and resilience), and proposed frameworks. An examination of the literature from a linguistic point of view was used. In this context, this study utilizes text mining analysis carried out by R Data Mining software and the analysis results are illustrated by word clouding technique. This study has the potential to increase researchers’ and managers’ decision-making capabilities by providing a roadmap for future research and practice.